A mathematical model describing the kinetic of cationic liposome production from dried lipid films adsorbed in a multitubular system - Torre,L. G. (2007)
Cationic liposomes are an alternative to DNA non-viral carrier in gene therapy, promoting higher efficiency for transport and delivery into the cells. Liposome production large scale is still a challenge. Among many processes, from dried film adsorbed inside multitubular system promising due its operational simplicity. this field, engineering contributions scarce no mathematical treatment literature describing type of process available. formulation proposed describe kinetic considering wetting disintegration lipid followed by lipids aggregation bilayers generating liposomes. model has fitted experimental data mass thickness, being useful predictions scaling up as well contributing development pharmaceutical products.